MERG1A Protein Abundance Increases in the Atrophied Skeletal Muscle of Denervated Mice, But Does Not Affect NFκB Activity. Issue 8 (7th August 2021) - Anderson, Luke B; Ravara, Barbara; Hameed, Sohaib; Latour, Chase D; Latour, Sawyer M; Graham, Valerie M; Hashmi, Mariam N; Cobb, Brittan; Dethrow, Nicole; Urazaev, Albert K; Davie, Judy K; Albertin, Giovanna; et al.
Abstract: Skeletal muscle atrophy may occur with disease, injury, decreased muscle use, starvation, and normal aging. No reliably effective treatments for atrophy are available, thus research into the mechanisms contributing to muscle loss is essential. The ERG1A K + channel contributes to muscle loss by increasing ubiquitin proteasome proteolysis (UPP) in the skeletal muscle of both unweighted and cachectic mice. Because the mechanisms which produce atrophy vary based upon the initiating factor, here we investigate atrophy produced by denervation. Using immunohistochemistry and immunoblots, we demonstrate that ERG1A protein abundance increases significantly in the Gastrocnemius muscle of rodents 7 days after both sciatic nerve transection and hind limb unweighting. Further, we reveal that ectopic expression of a Merg1a encoded plasmid in normal mouse Gastrocnemius muscle has no effect on activity of the NFκB transcription factor family, a group of proteins which contribute to muscle atrophy by modulation of the UPP. Further, although NFκB activity increases significantly after denervation, we show that expression of a plasmid encoding a dominant negative Merg1a mutant in Gastrocnemius muscle prior to denervation, has no effect on NFκB activity. Thus, although the ERG1A K + channel increases UPP, it does not do so through modulation of NFκB transcription factors.